Maize farmers’ response to crisis: The case of fall armyworm infestation in Ejisu Municipality, Ghana - Enoch Kwame Tham-Agyekum; Sebastian Kwabena Appiah; Fred Ankuyi; John-Eudes Andivi Bakang; Justice Frimpong-Manso; Padlass Patrick Edeafour; Maxwell Toah Asiamah (Cogent Social Sciences, 2023)
AbstractThe Fall Armyworm (FAW) is among the most devastating plant pests in terms of crop loss and economic impact. It was first reported in 2016 and has spread rapidly across the African continent, causing extensive damage to maize crops. With the importance of maize in food security and livelihoods, understanding effective communication channels is crucial. The study was designed to evaluate maize farmers’ communicative interventions in response to fall armyworm infestation in the Ejisu municipality. A multistage sampling procedure was adopted to select 400 maize farmers. Descriptive and econometric techniques were used to analyse the data. The maize farmers were knowledgeable about fall armyworm (FAW), and radio was their key source of information about FAW. Agricultural officers served as the most effective and preferred source of information about FAW. The outcomes obtained from the multivariate probit analysis reveal that the choice of communication intervention (thus, agricultural officers, radio, television and social media) is influenced by age, education, alternative livelihoods, access to credit, and cooperative society.1 Difficulty managing farms with poor planting distances2 was ranked as the greatest challenge in FAW management. The study highlights the need for maize farmers to consider indigenous communication interventions to supplement modern channels for effectively communicating and managing FAW infestations. Policymakers should prioritise the development of comprehensive communication strategies that integrate both modern and indigenous approaches to effectively disseminate information and enhance knowledge exchange among maize farmers in managing FAW outbreaks.